A general, versatile and divergent synthesis of selectively deuterated amines. Issue 33 (26th July 2021) - Lecomte, Morgan; Lahboubi, Mounsef; Thilmany, Pierre; El Bouzakhi, Adil; Evano, Gwilherm
Abstract : A general, versatile, divergent and metal-free synthesis of amines selectively deuterated at their α and/or β positions and relying on a simple treatment of ynamides with triflic acid and triethylsilane, either deuterated or not, is reported. Abstract : Deuterated organic molecules are of utmost importance in many areas of science and have been recently intensively investigated in medicinal chemistry due to their enhanced metabolic stability. The development of efficient and broadly applicable methods for the selective incorporation of deuterium atoms into organic molecules from readily available starting materials and reagents is therefore of extreme importance. Such methods however often lack generality and selectivity, notably in the nitrogen series. With nitrogen-containing molecules being indeed ubiquitous in medicinal chemistry, there is a strong need for efficient methods enabling the selective synthesis of deuterated amines. In this perspective, we report herein a general, versatile, divergent and metal-free synthesis of amines selectively deuterated at their α and/or β positions. Upon simple treatment of readily available ynamides with a mixture of triflic acid and triethylsilane, either deuterated or not, a range of amines can be smoothly obtained with high levels of deuterium incorporation by a unique sequence involving a domino keteniminium/iminium activation.